TO THE DEVELOPMENT OF MECHANICAL DESIGN STONE SPLITTING PRESS MKP-1 (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this work, new designs of a stone splitting mechanical press of the MKP-1 type were studied for the purpose of producing paving stones from stone waste collected in quarries in Kyrgyzstan for many years.Currently, interest in the processing of stone by splitting has increased not only due to its low energy intensity, but also due to the lower cost of the resulting product. As an analysis of the technological process of manufacturing chipped stone products by hand has shown, up to 10 hours of working time are spent on the production of one slab.Methods for creating calculation schemes and converting analytical expressions were used. A new design of a mechanical stone splitting press of the MKP-1 type has been substantiated and proposed. Its structure and operating principle are determined, and its advantages over analogues are shown. The results obtained make it possible to create a new mechanical stone splitting press, allowing the process of separating various stone products directly at the workplace and increasing the labor efficiency of stone cutters and builders.
Keywords: Natural stone; chipped products; portable mechanical stone splitting press; mechanical drive; frame